EVALUASI PENGGUNAAN LAHAN PERMUKIMAN PADA KAWASAN NEGATIVE LIST BERDASARKAN RENCANA TATA RUANG WILAYAH (RTRW) KOTA MANADO TAHUN 2014-2034 - Natan, Selfi; Kumurur, Veronica A.; Gosal, Pierre H. (MEDIA MATRASAIN, 2021)
Residential area is an area outside the protected area and is used as an environment settlements/community housing both in urban and in rural areas. Increase in number of population causes the needs for residential land also increases. Availability of land in a limited city causes the emergence of residential land that is not in accordance with the allotment. Similar to Indonesian cities, Manado City is also experiencing increase in population. In the 2011-2019 period, Manado City experienced an increase the total population is 21.399 people (BPS Manado City). With increasing number residents in the city of Manado then began to appear residential land located in the area that is not suitable for its designation. The purpose of this research is to identify the location of residential land use in the negative list area in Manado City and evaluate the use of PKP land in the negative list area. Technique Data collection used is observation, literature review, and documentation study. For analysis technique using spatial analysis techniques (overlay and descriptive). The results of this study is the use of residential land in the negative list area as much as 493,58 ha or 13,09% of the total existing settlements in Manado City. And for the suitability of residential land which is in the negative list area, namely in the less class area of 0,05 ha, for the sufficient class area of 446,78 ha, and the appropriate class area of 46,75 ha.